Sufficient conditions for the existence of oscillatory solutions to nonlinear second order differential equations - Sethi, Abhay Kumar; Ghaderi, Mehran; Rezapour, Shahram; Kaabar, Mohammed K. A.; İnç, Mustafa; Masiha, Hashem Parvaneh (Springer Heidelberg, 2022)
Some electrical events consist of mathematical models and due to the essence of electric current, their related differential equations have naturally an interesting property where all solutions are oscillatory. Many researchers have studied the necessary conditions for oscillatory solutions in the literature. But in this work, some sufficient conditions are investigated using Riccati transformation for nonlinear second order differential equations in which all solutions are oscillatory. Two illustrative examples are provided to validate our theoretical results. In addition, simulation results and numerical experiments are conducted to validate our obtained results.
Keywords: Oscillation; Positive differentiable function; Second order nonlinear equation; The Riccati transform